Role of MAPKs (mitogen activated protein kinases) in regulation of nucleation and organization of microtubules. - Damašková, Dagmar (Jihočeská univerzita, 2013)
The aim of the thesis is to review the current knowledge about MAPKs and their link to cytoskeleton namely to organization and nucleation of microtubules. In the experimental part I worked out scheme for activation of MAPKs and for drug induced inhibition. Specifically activation by hypo-osmotic shock and inhibition by U0126 were optimized in Arabidopsis thaliana cells and seedlings and detected by western blotting using antibodies recognizing specific active phosphorylated forms of MAPKs.
Role of MAPKs (mitogen activated protein kinases) in regulation of nucleation and organization of microtubules.
Keywords: mitogeny aktivované kinázy; mikrotubuly; gamma-tubulin; mitogen activated protein kinases; microtubules; gamma-tubulin